Patellofemoral dysbalance due to femoral deformities - diagnostic, therapy and results. Issue 3 (23rd March 2016) - Dickschas, Jörg; Strecker, Wolf; Harrer, Jörg; Ferner, Felix
Aims and Objectives: Anterior knee pain or patellofemoral instability are typical symptoms of patellofemoral dysbalance. Beside other reasons, this pathology can be caused by a femoral deformity. The two dimensions leading to this problems are torsional- and valgus deformities. This constellation often stays unrecognized. When diagnosed and analyzed, a femoral torsional or varization-osteotomy is the adequate treatment. Aim of this study was to show the diagnostic approach, the gold standard of therapy and the follow up results. Can patellofemoral stability be archived? Is the pain relief significant and how do clinical scores develop at the follow up? Materials and Methods: 33 femoral torsional osteotomies and 18 femoral varization osteotomies were included in this study, 5 of these were combined femoral varization and torsional corrections so that 46 knees are included in 41 patients, as 5 patients were operated on both legs. Major symptoms were patellofemoral dislocations in 28 cases and anterior knee pain in 26 cases. Beside clinical and radiographic evaluation full weight bearing long leg views and a torsional computertomography was always performed. Follow up examination was after 41 (6-113) months. Visual analog scala score, Japanese Knee Society Score, Tegner activity score and Lysholm score were taken before surgery and at the follow up. Results: Mechanical femorotibial valgus was on average 6, 4° (5°-10°), femoral internal torsion was in average 40, 9° (29°-66°; normal: 24°). Surgical treatment was performed with an arthroscopy followed by an acute femoral varization 7, 2°(5°-10°) and / or external torsion osteotomy of 13.8° (5°-26°). Tegner activity score, Japanese knee society score and Lysholm score all significantly improved. Pain relief could be demonstrated as shown by a significant decrease of the VAS score. No further dislocation was reported during the follow up period. Conclusion: Valgus or torsional deformities of the femur frequently lead to symptoms of the patellofemoral joint associated with anterior knee pain or instability. These deformities often stay undetected, leading to a long history of illness and surgical interventions not adressing the source of the symptoms. After thorough assessment and diagnostics a treatment plan involving an acute femoral varization / external torsion osteotomy should be scheduled. Correct surgical indication and performance leads to a significant pain relief and patellofemoral stability as can be demonstrated during follow up examination.